The impact of chromium ion stress on plant growth, developmental physiology, and molecular regulation - Saud, Shah; Wang, Depeng; Fahad, Shah; Javed, Talha; Jaremko, Mariusz; Abdelsalam, Nader R.; Ghareeb, Rehab Y. (Frontiers in Plant Science, 2022)
In the recent years, heavy metals induced soil pollution has been increased due to the widespread usage of chromium (Cr) in the chemical industry. The production of Cr into the environment reached at its peak level and become a serious heavy metal ion which is causing the hazardous environmental pollution. Heavy metal induced soil pollution is one of the most important abiotic stress affecting the dynamic stages of plant growth and development. In severe cases, it can kill the plants and their derivatives and similarly impose a potential threat to the human food safety. The chromium ion effect varies in plants and depend upon its severity range. It mainly disturbs the numerous regular activities of plant life cycle, by hindering the germination of plant seeds, inhibiting the growth of hypocotyl and epicotyl parts of plant, as well as damaging the chloroplast cell structures. In this review article, we tried to summarize the possible effects of chromium induced stress on plant growth, developmental physiology, biochemistry, and molecular regulation, and similarly provided the important theoretical basis for selecting the remedial plants in chromium-induced contaminated soils, breeding of low toxicity tolerant varieties, and analyzing the mechanism of plant resistance mechanisms in response to heavy metal stress.